Meningkatkan Keterampilan Menanam Sawi Hidroponik Melalui Metode Explicit Instruction Bagi Anak Tunagrahita Ringan - Khoirotulnisah, Khoirotulnisah; Z, Martias (Jurnal Penelitian Pendidikan Khusus, 2022)
This researce motivated by a problem that found in SLB Negeri Mandailing Natal, that a mild mental retardation student has dificultnes on knowing tools and materials and step for green cabbagebplanting. This research purpose for increasing skill in hydroponic green cabbage trough Explicit instruction method Classroom action research is approud in this research using by collaboration this method has two cycle and each cycle has for steps that in planning, action,observation, and reflection. Result of this research described on narration and grafhic that show about increasing planting skill in green cabbage by explicit instruction method. From the results of the study, it was found that the initial ability of the child's ability to increase from E 12,9% R 9,3% S 12,5% was then given action in the first cycle increasing E 57,8%, R 52,4 % S 56,9% then continued in the second cycle the child's ability increased to E 82,0%, R 79,6% S 78,1%. Result in this research show about study about planting skill on green cabbage by hydroponic formild mental retardasion in SLB Negeri Mandailing Natal. Teacher is recommended using this method for stdy bout Planting skill on green cabbage hydroponic